INTERCONNECTION OF INFLATION, BI RATE, AND EXCHANGE RATE ON MUDHARABAH AND MURABAHAH FINANCING - Early Ridho Kismawadi; Annisa Shafira Tania; Iskandar; M. Irvanni Bahri (Jurnal Ekonomi dan Bisnis Islam (Journal of Islamic Economics and Business), 2023)
The purpose of this study is to analyze the relationship between inflation, BI interest rates, and exchange rates on Mudharabah and Murabahah financing at Sharia Commercial Banks. This research is a quantitative study that applies the Johansen Integration Test and Vector Error Correction Model to see the long-term impact and shock response on certain variables. Research findings show that the exchange rate has a significant negative impact in the short term on Mudharabah financing income, while inflation factors and BI interest rates have a smaller negative impact in the short term. The receipt of Murabahah financing is negatively affected by all factors, especially inflation, BI interest rates, and currency exchange rates. Inflation and exchange rates have a significant negative impact in the long run on Mudharabah and Murabahah financing income, while BI interest rates have a small positive impact in the long run. Recommendations based on the results of this study are the importance of maintaining exchange rate stability and controlling inflation, as well as the need for effective risk management in the face of exchange rate fluctuations and inflation. In addition, Islamic banks need to improve operational efficiency, educate customers about economic risks, and encourage collaboration between relevant institutions for further research and better policy development.